Factors influencing webrooming intention of consumers: with special reference to northern province of srilanka - Ilangairasa, K. (University of Jaffna, 2022)
Purpose: This study aims to investigate the factors influencing the webrooming intention of consumers in the Northern Province of Sri Lanka, using widely accepted socio-psychological theory. Methodology: This research tested a conceptual framework derived from widely accepted theories. Questionnaire data were based on a sample of 232 Consumers from the Northern Province of Sri Lanka. The suggested research model was tested by using the quantitative way of analysis (Regression analysis) to examine the proposed hypothesis of this inquiry. Furthermore, online questionnaires were distributed to all the consumers in the Northern Province of Sri Lanka. Findings: The theoretical model was validated within the context of a single empirical study. The results indicated that perceived Ease of online search, Immediate Possession and Online Risk perception significantly influence on webrooming intention. Surprisingly, the authors documented that perceived Usefulness of Online Search, Need for Touch and Sales-staff Assistance have no significant influence on webrooming intention. Research limitations: This study relies on the cross-sectional survey-based data, future studies can therefore, examine the webrooming behaviour using longitudinal data or experimental study. Therefore, future research may use the proposed framework to examine webrooming phenomenon in other contexts for a deeper understanding of the consumer channel switching behaviour. Implications: This study has both theoretical and practical implications. The study makes several theoretical implications to the extant literature, webrooming intention is a crucial emerging challenge faced by multi-channel marketers, and however research on webrooming intention is still in its infancy. Therefore, this study enriches retailing literature by exploring the webrooming phenomenon. Finally, this study enriches the TAM literature by proposing a comprehensive conceptual model for a better understanding of the webrooming intention phenomenon. This study provides several practical implications for online retailers to manage consumer channel switching behaviour. The Findings of the study will help multi-channel retailers in designing their channel strategies for gaining competitive advantages. Webrooming is one of the crucial channel switching behaviour in the multi-channel retailing context and marketers are keen to know how they can consumers' webrooming-specific needs. In addition, this study will enable e-tailors to develop suitable strategies to convert webroomers into online buyers.
Keywords: Webrooming; Webrooming intention; Technology acceptance model